Fermi acceleration and its suppression in a time-dependent Lorentz gas - Oliveira, Diego F. M.; Vollmer, Juergen; Leonel, Edson Denis [UNESP] (Elsevier B.V., 2011)
Some dynamical properties for a Lorentz gas were studied considering both static and time-dependent boundaries. For the static case, it was confirmed that the system has a chaotic component characterized with a positive Lyapunov exponent. For the time-dependent perturbation, the model was described using a four-dimensional nonlinear map. The behaviour of the average velocity is considered in two different situations: (i) non-dissipative and (ii) dissipative dynamics. Our results confirm that unlimited energy growth is observed for the non-dissipative case. However, and totally new for this model, when dissipation via inelastic collisions is introduced, the scenario changes and the unlimited energy growth is suppressed, thus leading to a phase transition from unlimited to limited energy growth. The behaviour of the average velocity is described using scaling arguments. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Billiard; Lorentz gas; Lyapunov exponents; Fermi acceleration; Scaling